A retrospective study of snake bite envenomation in a tertiary care teaching hospital in Southern India - Murugan, Arul; Ahmed, Sarfaraz; Gani, Mohammad (International Journal of Research in Medical Sciences, 2017)
Background: Snake bite is an important occupational and rural hazard because India has always been a land of poisonous snakes. In southern India common poisonous snakes are Russell’s viper, Cobra, Krait and Saw Scaled Viper. It is a fact that despite of significant morbidity and mortality, very little attention is paid by the clinicians to this occupational hazard. The objective of the present study was undertaken with the objectives of assessing poisonous snake envenomation, ASV use, Dosage of ASV and clinical outcomes in snake bite victims. Methods: This is a Retrospective study of snakebite victims from November 2013 to April 2015 in a tertiary care teaching hospital in Tamil-Nadu. Results: A Total of 82 cases were studied in our hospital. Out of these 82 Poisonous bites, 42 (51.22%) cases were viper bites, 20 (24.39%) cases were unidentified poisonous bites, 16 (19.51%) cases were Krait, and 4 (4.88%) cases were Cobra. Coagulopathy, cellulitis, wound infection, renal failure and respiratory paralysis were the common complications. Average dose of ASV administered range from 8.57 (± 0.98) to 20.78 (± 4.18) Vials. An increase in mortality, ASV dose and complications were directly proportional to the Bite to ASV Administration time. Conclusions: Delay in hospitalization is associated with poor prognosis and increased mortality rate due to complications. There is an emergent need of awareness among the community for avoidance of traditional form of treatment and delay in early medical interventions.